2001
DOI: 10.1038/sj.bmt.1703262
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slow lymphocyte recovery and type of graft-versus-host disease prophylaxis on relapse after allogeneic bone marrow transplantation for acute myelogenous leukemia

Abstract: Summary:Allogeneic BMT is potentially curative for patients with acute myelogenous leukemia (AML) in first remission. However, many patients relapse after transplantation. Various immunotherapeutic options have been attempted with variable success in preventing relapse. Early identification of patients at high risk for relapse could allow prompt intervention. We examined the effect of slow lymphocyte recovery after siblingmatched allogeneic BMT on the risk of relapse in patients with AML. We also examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
47
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 43 publications
5
47
1
2
Order By: Relevance
“…The fact that a significant fraction of patients experienced durable remissions (some of whom whose cGVHD resolved) argues in favor of GVL effects active in the early post transplant period; this interpretation agrees with Kumar et al, who suggest that slow lymphocyte recovery after matched-sibling allogeneic BMT for AML predicts subsequent relapse. [46][47][48][49][50] In fact, the overall relapse rate of 30.0% at 4.7 years is comparable to that observed with RIC regimens or conventional allotransplantation. 1,[51][52][53] The particularly low relapse rate with MUD transplants (9%) suggests that given sufficient immunosuppression to effect engraftment, the risk of progression/relapse after MUD transplantation may be more fundamentally susceptible to increases in GVHD preventive intensity than the relative strength of conditioning.…”
Section: Discussionmentioning
confidence: 59%
“…The fact that a significant fraction of patients experienced durable remissions (some of whom whose cGVHD resolved) argues in favor of GVL effects active in the early post transplant period; this interpretation agrees with Kumar et al, who suggest that slow lymphocyte recovery after matched-sibling allogeneic BMT for AML predicts subsequent relapse. [46][47][48][49][50] In fact, the overall relapse rate of 30.0% at 4.7 years is comparable to that observed with RIC regimens or conventional allotransplantation. 1,[51][52][53] The particularly low relapse rate with MUD transplants (9%) suggests that given sufficient immunosuppression to effect engraftment, the risk of progression/relapse after MUD transplantation may be more fundamentally susceptible to increases in GVHD preventive intensity than the relative strength of conditioning.…”
Section: Discussionmentioning
confidence: 59%
“…4 Other studies have not demonstrated significantly improved immune reconstitution with RIC, 5,6 making this area a subject of continued debate (reviewed by Jimenez et al 7 ). While many previous studies of immune reconstitution post HSCT have focused on lymphocyte subset recovery, [8][9][10][11][12][13][14][15][16] we have previously shown that combined monocyte and lymphocyte recovery also has an impact on survival post myeloablative HSCT in acute leukemia due to a reduction in nonrelapse mortality. 17 Here, we test the hypothesis that both lymphocyte and monocyte recovery are similarly associated with survival in patients undergoing RIC allogeneic HSCT with fludarabine and melphalan.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Previous studies have shown that delayed lymphocyte recovery post-allogeneic HSCT is associated with increased risk of relapse in acute myelogenous and lymphoid leukemia in adults. [8][9][10][11][12] The clinical induction of GVL effect offers a new approach for patients who relapse post-HSCT. 13 This has most commonly been as donor lymphocyte infusion (DLI), and several reports have demonstrated long-term survival with this approach.…”
Section: Introductionmentioning
confidence: 99%